Exploring the Relationship between Self-Concept, Adjustment and Parenting Styles in Adolescents - Ms. Parul Nagar; Dr. Ambrien Ahmed (The Bioscan, 2024)
This study examines the relationship between self-concept, adjustment, and parenting styles among adolescent students. A sample of 110 adolescents aged 14–18 years was selected using convenience sampling from local schools and colleges. The Self-Concept Questionnaire by R.K. Saraswat, the Adjustment Inventory for School Students (AISS) by Sinha and Singh, and Multi-Dimensional Parenting Style Scale by Chauhan & Khokhar were used to assess self-concept, adjustment, and parenting styles, respectively. The findings suggest that positive parenting styles, such as acceptance and encouragement, significantly contribute to better emotional and social adjustment among adolescents. Democratic parenting was associated with improved interpersonal skills, while autocratic parenting exhibited a complex influence, enhancing educational adjustment but negatively impacting moral self-concept. These results highlight the role of parenting in fostering adolescents’ resilience, confidence, and decision-making abilities.